Barneys New York : a case of "shop and frisk" - Cellante, Christopher; Kelly, Timothy; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
In late 2013, Barneys New York quickly found itself embroiled in controversy. Within the span of a few days, Barneys CEO Mark Lee's attention shifted from ensuring record breaking holiday sales to a lawsuit, an Attorney Generals investigation, a potential boycott, and his company's biggest holiday contract hanging in the balance. News media and political activists labeled Barneys a racist brand, and Lee needed to find a way to regain the trust of customers and the public at large.
Originally published in Cellante, C., Kelly, T., & ORourke, J. S. (2015). Barneys New York: A case of "shop and frisk." 15-01. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame Communication, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Barneys New York; Customer relations; Corporate image; Retail trade